An adaptive voltage‐regulation control strategy of an electric spring based on output current feedback. Issue 3 (15th October 2018) - Chen, Yixi; Ma, Gang; Wang, Ying; Xu, Guchao
Abstract : With the increasing penetration of distributed generation (DG) in power systems, the voltage instability problem of power systems is receiving a great deal of attention. As new power electronics equipment, an electric spring (ES) can effectively restrain the bus voltage fluctuation caused by DG, and in addition achieve the new control paradigm of load demand following power generation. In this article, an adaptive voltage‐regulation control strategy of ES is proposed, in which the proportional integral (PI) postgain changes dynamically according to the real‐time output current of the ES. The simulation results show that, when the proposed control strategy is applied, bus voltage can still be stabilized effectively by the ES under the condition that noncritical loads change. The proposed control strategy brings the adaptive voltage‐regulation capability of the ES, and therefore, it can be in series with multiple noncritical loads reliably and safely, and accordingly the costs can be greatly reduced. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.